2008
DOI: 10.1590/s1413-70542008000400013
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos de fontes e doses de silicato de cálcio no rendimento agrícola e na qualidade tecnológica da cana-de-açúcar, cultivar SP80-1816

Abstract: Com o objetivo de estudar os efeitos da aplicação de diferentes fontes e doses de silicato de cálcio na cultura da cana-de-açúcar, cultivar SP80-1816, instalou-se um experimento num Latossolo Vermelho Amarelo distrófico, em área localizada no alambique João Mendes - "JM" (Sítio Vó Zirica), no Município de Perdões, Estado de Minas Gerais. O delineamento experimental utilizado foi o de blocos ao acaso, quatro repetições, esquema fatorial 3x3+1, sendo três fontes de silicato de cálcio (Silifértil, Extrativa e Agr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
1
1
0
4
Order By: Relevance
“…In addition, in during plant-cane crop, there was no water restriction ( Figure 1) which favored the crop growth. Similar results were found by Leite et al (2008), who found no effect of up to 450 kg of calcium silicate on sugarcane yield in an area with annual precipitation of 1493 mm.…”
Section: Stalk and Sugar Yieldsupporting
confidence: 88%
“…In addition, in during plant-cane crop, there was no water restriction ( Figure 1) which favored the crop growth. Similar results were found by Leite et al (2008), who found no effect of up to 450 kg of calcium silicate on sugarcane yield in an area with annual precipitation of 1493 mm.…”
Section: Stalk and Sugar Yieldsupporting
confidence: 88%
“…A infestação (I) de broca-da-cana-de-açúcar foi feita por meio da contagem de número de entrenós totais (T) e atacados (A), utilizando, posteriormente, a fórmula: I= A/T *100. A produção de colmos foi efetuada pela pesagem dos colmos, realizando-se a estimativa de massa por parcela em toneladas por hectare, conforme feito por Leite et al (2008).…”
Section: Methodsunclassified
“…In this case, depending on the order of the traits, this genotype may present a very large or very small area, which may be indicative of a disturbing factor for the breeder (i.e., some traits present discrepant values that make the interval larger). The visualization of this genotype suggests that this disturbance was due to a very low FIB content compared to the other traits [Leite et al (2008) also found low FIB for this genotype]. This caused greater variation in the polygon area based on trait order, and consequently a larger interval.…”
Section: Aimentioning
confidence: 76%